ATTEMPTING TO REGISTER CHANGES: THE EDUCATIONAL DIMENTION OF CONTEMPORARY SOCIETIES - BARANOWSKI, MARIUSZ; ODROWĄŻ-COATES, ANNA (Society Register, 2018)
When registering the changes affecting our societies, which undoubtedly have a multidimensional character and occur at different speeds, it is impossible to disregard the issue of education. This is especially true in the context of the discourse focusing on so-called cognitive capitalism, creative industries, intangible work, gig/sharing economy, education is an extremely important element of not only “the personal troubles”, but also “the public issues of social structure”, to use C. Wright Mills (2000:8) terms.